The Association of Occupation and Income with The Incidence of Stunting - Fitriani, Fifin Dewi; Sunarsih, Tri; Yulaikhah, Lily (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2024)
Stunting is the most common form of child malnutrition worldwide, affecting 161 million children aged 0 to 5 years. One way to look at a community's general health condition is through the socioeconomic status within that group. This study aimed to determine the relationship between occupation and income with the incidence of stunting in the Ngalang sub-district. The design of this study was cross-sectional with a population of 85 parents who had toddlers aged 0-60 months with stunting conditions in Ngalang Village, Gunungkidul Yogyakarta. The sampling technique used was purposive sampling with the Slovin method with an error tolerance of 10percent, so the sample size was 46 parents and stunted toddlers who met the inclusion criteria. Data were analysed using Spearman's rho test. The results showed that the father's job was p equal 0.021, the mother's job was p equal 0.70, and the family income was p equal 0.023. There is an association between father's occupation and family income on the condition of stunted toddlers. However, there is no relationship between the mother's job and the condition of stunted toddlers in Ngalang Village. The advice given in this study is that families with stunted toddlers should look for opportunities to increase family income, such as finding additional work or starting a small business from home.